Bailing on the Car That Was Not Bailed Out: Bounding Consumer Reactions to Financial Distress. Issue 2 (7th December 2016) - Huse, Cristian; Koptyug, Nikita
Abstract : We examine how consumers react to the financial distress of durable goods manufacturers by studying the Swedish new car market. We employ a difference‐in‐differences matching methodology whereby we compare sales of carmaker Saab with those of a control group of substitute products. To account for possible substitution between products in the treatment and control groups, we propose and apply bounds to our difference‐in‐differences matching estimator. We then refine the bounds and provide conditions under which they depend only on product elasticities. We find that there was a significant decrease in the sales of Saab following its filing for administration.